1977
DOI: 10.1063/1.861734
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity and turbulence production in pattern recognized turbulent flow structures

Abstract: A pattern recognition technique has been applied to data obtained in a turbulent channel flow. The u signal patterns are recognized using several simple criteria, but simultaneously, other signals are processed. A newly designed probe provides, in addition to simultaneous u, v, and w signals, vorticity signals, ωz and ωy, and a signal which can be interpreted as the instantaneous turbulence production, uv (∂U/∂y). The ensemble averaged results provide insight into the vorticity dynamics and turbulence producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 0 publications
3
17
0
1
Order By: Relevance
“…The scheme also normalized each pattern to an arbitrarily chosen time interval (the maximum and minimum slopes of the pattern were fixed at two predetermined points along this interval). Always using u to detect the pattern, conditional averages were obtained (see Eckelmann et al 1977), over the same i�terval, for a number of signals including the instantaneous spanwise vorticity and the instantaneous turbulence pro duction. The v signal was on average 1800 out-of-phase with the u signal (as noted by Blackwelder & Kaplan 1976) and the ejection was found to be the principal producer of turbulent energy.…”
Section: Conditional Sampling and Averaging Of Coherent Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The scheme also normalized each pattern to an arbitrarily chosen time interval (the maximum and minimum slopes of the pattern were fixed at two predetermined points along this interval). Always using u to detect the pattern, conditional averages were obtained (see Eckelmann et al 1977), over the same i�terval, for a number of signals including the instantaneous spanwise vorticity and the instantaneous turbulence pro duction. The v signal was on average 1800 out-of-phase with the u signal (as noted by Blackwelder & Kaplan 1976) and the ejection was found to be the principal producer of turbulent energy.…”
Section: Conditional Sampling and Averaging Of Coherent Structuresmentioning
confidence: 99%
“…The v signal was on average 1800 out-of-phase with the u signal (as noted by Blackwelder & Kaplan 1976) and the ejection was found to be the principal producer of turbulent energy. Eckelmann et al (1977) suggested that the interesting dynamics occur during the acceleration phase of the pattern. It should also be noted that conditional sampling based on quadrant analysis (Section 3) can be used to provide reference times (when the threshold level is exceeded in the relevant quadrant) for the event.…”
Section: Conditional Sampling and Averaging Of Coherent Structuresmentioning
confidence: 99%
“…For a number of years, many researchers have developed and refined the design of multi-sensor probes in order to provide a suitable scheme measuring all vorticity components (Eckelman et al [19]). The development of the multi-sensor probe measuring technique appears to answer satisfactorily the question of simultaneous recording of the mean and turbulent characteristics of the three-dimensional velocity-vorticity flow field.…”
Section: Multi Sensor Hwa For Vorticity Measurementsmentioning
confidence: 99%
“…Klewicki et al (1992) used the same method in an attempt to study the cross-stream vorticity components in a turbulent boundary layer. Eckelmann et al (1977) proposed a five sensor arrangement in order to obtain, simultaneously, the two components of vorticity. Wassman and Wallace (1979), Vukoslavcevic et al (1991), Balint e; a/ (1991) and Andreopoulos and Honkan (1996), among others, attempted three component simultaneous measurements of the vorticity vector using various configurations of clusters of hot-wire sensors, the latter three using nine independent wires in groups of three at spatially distinct locations.…”
Section: Current State-of-the-artmentioning
confidence: 99%